Cooperation between child care and criminal justice agencies in case of sex offences against children: developing a model concept for the implementation of children's rights to criminal procedure; abridged version - Dawid, Evelyn; Elz, Jutta; Haller, Birigitt (KrimZ, 2010)
Children who become victims of sex offenses are entitled to protection and assistance, not only from children and youth services but from police, public prosecution and court – therefore from a large number of institutions with different (legal) contracts, organisational structures, self-conceptions, interests and terminologies. Despite the common target, the cooperation of several institutions and different professions is not always easy. From 2008 to 2010, a research project, partially funded by the European Commission, was conducted by researchers from the Centre for Criminology, Lucerne University and the Institute of Conflict Research in Vienna to study current approaches to interdisciplinary cooperations on sex offenses against children in the three participating countries – Germany, Switzerland and Austria. The overall goal was to develop a model concept for interdisciplinary cooperations on sex offences against children with the participation of public children and youth services and criminal justice. This final report presents the findings of the study. An extended version, only issued in German, is published as volume 60 in the series of Kriminologie und Praxis (KUP). It is characterised primarily by much larger country reports and to a much broader representation of the data collected.